KUALITAS SUMBER DAYA MANUSIA DALAM MENINGKATKAN PEMBANGUNAN DESA TINGGILBET DISTRILK BEOGA KABUPATEN PUNCAK PROVINSI PAPUA - KULLA, TENIUS; RUMAPEA, PATAR; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this study to find out how the implementation of quality human resources management inimproving the development of Tingilbet Village District Beoga District Peak Papua Province. The method usedin this study using descriptive qualitative methods. to understand a phenomenon in a social context naturallyby promoting a deep process of interaction and communication between researchers with the phenomenastudied. As for the results of research shows that the implementation of quality human resources managementin improving the development of employee recruitment, staffing and staff development is still minimal in thegovernment environment of Tinggilbet Village Beoga District is not fully done objectively and in accordancewith the needs and expertise of the employees themselves, the implementation of recruitment employee,employee placement and employee development, according to the result of research that has not been done well.KEYWORDS: quality of human resources, village develop